Determinants of personal hygiene behavior amongst food handlers in fast food restaurants in South Jakarta, Indonesia - Avifah, Shelvira; Fitria, Laila (Universitas Gadjah Mada, 2025)
Purpose: This study aimed to analyze the association between hygiene and sanitation facilities, food handler knowledge, health checks, and uniform conditions with personal hygiene behavior among food handlers in fast food restaurants in South Jakarta. Methods: A cross-sectional study was conducted using secondary data from 102 fast food restaurants inspected by the South Jakarta Health Office in 2021. Variables were constructed from standardized environmental health inspection forms. Chi-square tests and logistic regression were used to analyze the relationships between variables. Results: The majority (93.1%) of food handlers exhibited good personal hygiene behavior. Multivariate analysis revealed that the quantity and quality of handwashing facilities (adjOR: 6.64; 95% CI: 1.14–38.74) and the condition of work uniforms (adjOR: 8.48; 95% CI: 1.43–50.12) were significantly associated with personal hygiene behavior. Other variables, such as knowledge and health checks, showed no significant association despite low implementation rates. Conclusion: Ensuring the availability of proper handwashing facilities and appropriate work uniforms can significantly improve food handlers’ hygiene behavior, thereby reducing the risk of foodborne illnesses. These findings underline the importance of infrastructure, routine inspections, and hygiene monitoring in fast food settings as part of a broader public health strategy to enhance food safety.